2020
DOI: 10.2174/1871530319666191018124710
|View full text |Cite
|
Sign up to set email alerts
|

Arg753Gln Polymorphisms in the Toll-Like Receptor 2 Gene are Associated with Cytomegalovirus Infection in Egyptian Bone Marrow Recipients

Abstract: Background: Previous studies have shown that cytomegalovirus (CMV) induced innate immune response via activation of Toll-like receptor 2 (TLR2). The association between CMV among specific single-nucleotide polymorphisms (SNPs) in the TLR2 gene was also investigated. Objective: This study investigated the relationship between specific SNPs in the TLR2 gene (G>A), TLR2-Arg753Gln (rs5743708), and CMV replication after bone marrow transplantation. Methods: The TLR2-Arg753Gln SNP was genotyped in 181 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Similarly, El-Nabi et al 31 reported that the Arg753Gln variant in the TLR2 gene was linked to CMV infection in Egyptian bone marrow recipients. They showed that 85% of the patients screened were G/G homozygous, whereas 15% were G/A heterozygous; there were no patients that were homozygous for (A/A).…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, El-Nabi et al 31 reported that the Arg753Gln variant in the TLR2 gene was linked to CMV infection in Egyptian bone marrow recipients. They showed that 85% of the patients screened were G/G homozygous, whereas 15% were G/A heterozygous; there were no patients that were homozygous for (A/A).…”
Section: Discussionmentioning
confidence: 92%
“…1 In the last few decades, important measures have been adopted to control and prevent viral infections across the globe. 2,3 These measures include the introduction of a safe and effective vaccine against HBV infection for all newborns and high-risk groups in all WHO member countries, screening of blood and blood derivatives 4 and the implementation of more efficient tests such as nucleic acid testing (NAT). 5 In addition, treatments for chronic HBV infection have been updated and their efficiency improved.…”
Section: Introductionmentioning
confidence: 99%
“…The valvuloseptal heart defect may occur due to disruptions in the signal transformation of endocardial cushions [12]. TGFBR2 is expressed during heart development in embryonic myocytes, endothelial cells, and endocardial cushion of mice [13].…”
Section: Introductionmentioning
confidence: 99%